A Unified Framework for DPLL(T) + Certificates. (23rd May 2013) - Zhou, Min; He, Fei; Wang, Bow-Yaw; Gu, Ming; Sun, Jiaguang
Abstract : Satisfiability Modulo Theories (SMT) techniques are widely used nowadays. SMT solvers are typically used as verification backends. When an SMT solver is invoked, it is quite important to ensure the correctness of its results. To address this problem, we propose a unified certificate framework based on DPLL(T ), including a uniform certificate format, a unified certificate generation procedure, and a unified certificate checking procedure. The certificate format is shown to be simple, clean, and extensible to different background theories. The certificate generation procedure is well adapted to most DPLL(T )-based SMT solvers. The soundness and completeness for DPLL(T ) + certificates were established. The certificate checking procedure is straightforward and efficient. Experimental results show that the overhead for certificates generation is only 10%, which outperforms other methods, and the certificate checking procedure is quite time saving.